NOD1 in the modulation of host–microbe interactions and inflammatory bone resorption in the periodontal disease model - Chaves de Souza, João Antônio [UNESP]; Frasnelli, Sabrina Cruz Tfaile [UNESP]; Curylofo-Zotti, Fabiana de Almeida [UNESP]; Ávila-Campos, Mário Julio; Spolidório, Luis Carlos [UNESP]; Zamboni, Dario Simões; Graves, Dana T.; Rossa, Carlos [UNESP] (Wiley, 2016)
Periodontitis is a chronic inflammatory condition characterized by destruction of non-mineralized and mineralized connective tissues. It is initiated and maintained by a dysbiosis of the bacterial biofilm adjacent to teeth with increased prevalence of Gram-negative microorganisms. Nucleotide-binding oligomerization domain containing 1 (NOD1) is a member of the Nod-like receptors (NLRs) family of proteins that participate in the activation of the innate immune system, in response to invading bacteria or to bacterial antigens present in the cytoplasm. The specific activating ligand for NOD1 is a bacterial peptidoglycan derived primarily from Gram-negative bacteria. This study assessed the role of NOD1 in inflammation-mediated tissue destruction in the context of host–microbe interactions. We used mice with whole-genome deletion of the NOD1 gene in a microbe-induced periodontitis model using direct injections of heat-killed Gram-negative or Gram-negative/Gram-positive bacteria on the gingival tissues. In vitro experiments using primary bone-marrow-derived macrophages from wild-type and NOD1 knockout mice provide insight into the role of NOD1 on the macrophage response to Gram-negative and Gram-negative/Gram-positive bacteria. Microcomputed tomography analysis indicated that deletion of NOD1 significantly aggravated bone resorption induced by Gram-negative bacteria, accompanied by an increase in the numbers of osteoclasts. This effect was significantly attenuated by the association with Gram-positive bacteria. In vitro, quantitative PCR arrays indicated that stimulation of macrophages with heat-killed Gram-negative bacteria induced the same biological processes in wild-type and NOD1-deficient cells; however, expression of pro-inflammatory mediators was increased in NOD1-deficient cells. These results suggest a bone-sparing role for NOD1 in this model.
Keywords: bone resorption; host–microbe interactions; inflammation; innate immunity; NOD1